TGF-β1 relieves burn injury induced pain by alleviating inflammation in mouse - Shengfeng Gao; Mengting Wang; Lu Wang; Yasu Jiang; Peng Chen; Li Guo; Lili Ni; Fan Fei; Zhenhua Gong (PLoS ONE, 2026)
Burn injuries are severe traumas characterized by tissue damage and inflammation, and pain is the common symptom of burn patients. Transforming growth factor beta 1 (TGF-β1) is a multifunctional cytokine involved in organ development, immune response, tumor biology and injury repair. This study investigates the effects of TGF-β1 on the burn injury induced pain and explore the underlying mechanisms. A mouse model of second degree burn injury was established, and spinal intrathecal injection with lentivirus was used to knockdown or overexpress TGF-β1. The assessment of mechanical allodynia and thermal hyperalgesia was adapted to evaluate the impact of TGF-β1 on the burn injury induced pain. The expressions of inflammatory factors were measured by using RT-qPCR, while immunofluorescence staining was employed to detect the effects of TGF-β1 on macrophage infiltration in the burned plantar skin. Western blot was used to analyze the effects of TGF-β1 on microglia, astrocytes and signal pathway. RT-qPCR results demonstrated that lentiviruses injection could knockdown or overexpress TGF-β1 in ipsilateral spinal cord, and reduce pro-inflammatory factors (IL-1β, IL-6 and TNF-α) expression and promote anti-inflammatory factor (IL-10) expression. The behavioral assessments revealed that TGF-β1 overexpression alleviated mechanical allodynia and thermal hyperalgesia. Immunofluorescence staining and Western blot revealed that TGF-β1 reduced the macrophage infiltration in the plantar skin, inhibited expressions of marker proteins of microglia and astrocyte, and promoted the phosphorylation of smad2. These findings suggested that TGF-β1 mitigated burn injury induced pain by attenuating inflammatory response via TGF-β1/smad2 pathway. This study provides an experimental and theoretical basis supporting the potential use of TGF-β1 as an anti-inflammatory and analgesic for burn injury.